Differences in Health Care Needs, Health Care Utilization, and Health Care Outcomes Among Children With Special Health Care Needs in Ohio: A Comparative Analysis Between Medicaid and Private Insurance. Issue 1 (January 2017) - Sarkar, Madhurima; Earley, Elizabeth R.; Asti, Lindsey; Chisolm, Deena J.
Abstract : Objective: This study explores comparative differentials in health care needs, health care utilization, and health status between Medicaid and private/employer-sponsored insurance (ESI) among a statewide population of children with special health care needs (CSHCN) in Ohio. Methods: We used data from the 2012 Ohio Medicaid Assessment Survey to examine CSHCN's health care needs, utilization, status, and health outcomes by insurance type. Adjusted multivariable logistic regression models were used to explore associations between public and private health insurance, as well as the utilization and health outcome variables. Results: Bivariate analyses indicate that the Medicaid population had higher care coordination needs (odds ratio [OR] = 1.6; 95% confidence interval [CI], 1.1-2.2) as well as need for mental/educational health care services (OR = 1.5; 95% CI; 1.1-2.0). They also reported higher unmet dental care needs (OR = 2.2; 95% CI, 1.2-4.0), higher emergency department (ED) utilization (OR = 2.3; 95% CI, 1.7-3.2), and worse overall health (OR = 0.6; 95% CI, 0.4-0.7), oral health (OR = 0.4; 95% CI, 0.3-0.5), and vision health (OR = 0.4; 95% CI, 0.2-0.6). After controlling for demographic variables, CSHCN with Medicaid insurance coverage were more likely to need mental health and education services (adjusted odds ratio [AOR] = 1.8; 95% CI; 1.2-2.6), had significantly more ED visits (AOR = 2.3; 95% CI, 1.5-3.5), and were less likely to have excellent overall health (AOR = 0.64; 95% CI, 0.4-0.9), oral health (AOR = 0.43; 95% CI, 0.3-0.7), and vision health (AOR = 0.38; 95% CI, 0.2-0.6) than those with private insurance/ESI. Conclusion: The CSHCN population is a highly vulnerable population. While Ohio's Medicaid provides greater coverage to CSHCN, disparities continue to exist within access and services that Medicaid provides versus the ones provided by private insurance/ESI.